CASSAVA-BASED BIOPLASTIC AS A CARRIER MEDIUM FOR SLOW-RELEASE FERTILIZER - Yudi, Yulius; Syahbanu, Intan; Wahyuni, Nelly (Walisongo Journal of Chemistry, 2025)
The rapid nutrient release of conventional fertilizers often leads to resource inefficiency, environmental pollution, and a continuous increase in subsidized fertilizer demand in Indonesia. This study aimed to develop cassava starch (Manihot esculenta Crantz)-based bioplastic as a carrier medium for urea slow-release fertilizer (SRF). The bioplastic was further analyzed for its mechanical properties, biodegradability, and nutrient release efficiency. The research method involved cassava starch preparation, bioplastic fabrication using cassava starch, polyvinyl alcohol (PVA), and glycerol mixtures, followed by testing of water resistance, tensile strength, elongation, Fourier Transform Infrared (FTIR) analysis, and SRF release performance. The results showed that bioplastic containing fertilizer (BP) exhibited higher water absorption, with water resistance of 73.45%, compared to bioplastic without fertilizer (BP0), which showed 67.44% water resistance. Mechanical testing revealed that bioplastic without fertilizer had a higher tensile strength (0.99 MPa) than bioplastic containing fertilizer (0.50 MPa). Although the tensile strength did not meet the Indonesian National Standard (SNI ISO 527-1:2016), which requires values between 24.7–302 MPa, the elongation properties of both samples met the standard range of 21–220%. Functional group analysis using FTIR indicated changes in the chemical structure of the bioplastic due to fertilizer addition, evidenced by a shift in the FTIR absorption peak at 2164.13 cm⁻¹, corresponding to the isocyanate group. The urea slow-release test conducted over six days showed a nutrient release efficiency of 66% for the bioplastic-embedded urea fertilizer (BP) compared to the direct use of urea fertilizer. Overall, this study demonstrates that cassava starch-based bioplastic has strong potential as an efficient carrier material for SRF applications.